I was asked to expand on my comments with a more detailed answer, so here goes:
Part (a)
![](https://latex.codecogs.com/png.latex?\bg_white \begin{align*} x^3 - 3x - 1 &= 0 \qquad \qquad \text{. . . . . (*)} \\ \\ \text{Let $x = \frac{p}{q}$, where $p$ and $q$ are coprime and $pq \neq 0$, be a root of} \qquad ax^3 - 3x + b &= 0 \qquad \text{where $a$, $b \in \mathbb{Z}$} \\ a\left(\frac{p}{q}\right)^3 - 3\left(\frac{p}{q}\right) + b &= 0 \\ \frac{ap^3}{q^3} - \frac{3p}{q} + b &= 0 \\ ap^3 - 3pq^2 + bq^3 &= 0 \\ \\ \text{This statement may be expressed as} \qquad ap^3 &= 3pq^2 - bq^3 = q^2(3p - bq) \quad \quad \text{. . . . . (1)} \\ \text{Or, alternatively, as} \qquad bq^3 &= 3pq^2 - ap^3 = p(3q^2 - ap^2) \quad \quad \text{. . . . . (2)} \end{align*})
Now,
![](https://latex.codecogs.com/png.latex?\bg_white q)
is clearly a factor of the RHS of statement (1), and so must also be a factor of
![](https://latex.codecogs.com/png.latex?\bg_white \text{LHS}\ = ap^3)
. However, with
![](https://latex.codecogs.com/png.latex?\bg_white p)
and
![](https://latex.codecogs.com/png.latex?\bg_white q)
being coprime (and so sharing no factors other than
![](https://latex.codecogs.com/png.latex?\bg_white \pm 1)
, it follows that either
![](https://latex.codecogs.com/png.latex?\bg_white q = \pm 1)
or
![](https://latex.codecogs.com/png.latex?\bg_white q)
is a factor of
![](https://latex.codecogs.com/png.latex?\bg_white a)
. In either case,
![](https://latex.codecogs.com/png.latex?\bg_white q)
divides
![](https://latex.codecogs.com/png.latex?\bg_white a)
.
Similarly,
![](https://latex.codecogs.com/png.latex?\bg_white p)
is clearly a factor of the RHS of statement (2), and so must also be a factor of
![](https://latex.codecogs.com/png.latex?\bg_white \text{LHS}\ = bq^3)
. However, with
![](https://latex.codecogs.com/png.latex?\bg_white p)
and
![](https://latex.codecogs.com/png.latex?\bg_white q)
being coprime (and so sharing no factors other than
![](https://latex.codecogs.com/png.latex?\bg_white \pm 1)
, it follows that either
![](https://latex.codecogs.com/png.latex?\bg_white p = \pm 1)
or
![](https://latex.codecogs.com/png.latex?\bg_white p)
is a factor of
![](https://latex.codecogs.com/png.latex?\bg_white b)
. In either case,
![](https://latex.codecogs.com/png.latex?\bg_white p)
divides
![](https://latex.codecogs.com/png.latex?\bg_white b)
.
The equation (*) is the same equation with
![](https://latex.codecogs.com/png.latex?\bg_white a = 1)
and
![](https://latex.codecogs.com/png.latex?\bg_white b = -1)
. For this equation to have a rational root requires
![](https://latex.codecogs.com/png.latex?\bg_white q)
divides
![](https://latex.codecogs.com/png.latex?\bg_white a = 1)
and
![](https://latex.codecogs.com/png.latex?\bg_white p)
divides
![](https://latex.codecogs.com/png.latex?\bg_white b = -1)
or that they are
![](https://latex.codecogs.com/png.latex?\bg_white \pm 1)
. In other words, the only possible rational roots of (*) are
![](https://latex.codecogs.com/png.latex?\bg_white x = \pm 1)
. However:
![](https://latex.codecogs.com/png.latex?\bg_white \begin{align*} \text{Test $x = 1$ in (*):} \qquad \text{LHS} &= x^3 - 3x - 1 = 1^3 - 3(1) - 1 = 1 - 3 - 1 = -3 \neq 0 \qquad \implies \qquad x = 1\ \text{is not a root of (*)} \\ \text{Test $x = -1$ in (*):} \qquad \text{LHS} &= x^3 - 3x - 1 = (-1)^3 - 3(-1) - 1 = -1 + 3 - 1 = 1 \neq 0 \quad \implies \quad x = -1\ \text{is not a root of (*)} \end{align*})
Hence, the equation (*) has no rational roots.
Part (b)
![](https://latex.codecogs.com/png.latex?\bg_white \begin{align*} \text{Let $x = r + s\sqrt{d}$ be a root of (*):} \qquad \left(r + s\sqrt{d}\right)^3 - 3\left(r + s\sqrt{d}\right) - 1 &= 0 \qquad \text{where $r$, $s$, and $d \in \mathbb{Q}$ but $\sqrt{d} \notin \mathbb{Q}$} \\ r^3 + 3r^2s\sqrt{d} + 3r\left(s\sqrt{d}\right)^2 + \left(s\sqrt{d}\right)^3 -3r - 3s\sqrt{d} - 1 &= 0 \\ r^3 + 3r^2s\sqrt{d} + 3rs^2d + s^3d\sqrt{d} - 3r - 3s\sqrt{d} - 1 &= 0 \\ \left(r^3 + 3rs^2d - 3r - 1\right) + s\sqrt{d}\left(3r^2 + s^2d - 3\right) &= 0 \\ \text{Since $\sqrt{d} \notin \mathbb{Q}$ and thus $d \neq 0$, this can only be true if} \qquad s\sqrt{d}\left(3r^2 + s^2d - 3\right) &= 0 \\ 3r^2s + s^3d - 3s &= 0 \qquad \text{as required} \end{align*})
In fact, since
![](https://latex.codecogs.com/png.latex?\bg_white s \neq 0)
(as that would make the root being tested rational, which is impossible from part (a)), we have actually shown that
![](https://latex.codecogs.com/png.latex?\bg_white 3rs + s^2d - 3 = 0)
, and also that
![](https://latex.codecogs.com/png.latex?\bg_white r^3 + 3rs^2d - 3r - 1 = 0)
.
Testing
![](https://latex.codecogs.com/png.latex?\bg_white x = r - s\sqrt{d})
will yield
![](https://latex.codecogs.com/png.latex?\bg_white \text{LHS} = \left(r^3 + 3rs^2d - 3r - 1\right) - s\sqrt{d}\left(3r^2 + s^2d - 3\right) = 0)
using these results, confirming that it must also be a root.
Knowing that two of the roots are
![](https://latex.codecogs.com/png.latex?\bg_white \alpha = r + s\sqrt{d})
and
![](https://latex.codecogs.com/png.latex?\bg_white \beta = r - s\sqrt{d})
and setting the third root to
![](https://latex.codecogs.com/png.latex?\bg_white \gamma)
, it follows that
![](https://latex.codecogs.com/png.latex?\bg_white \begin{align*} \alpha + \beta + \gamma &= -\frac{0}{1} \\ \left(r + s\sqrt{d}\right) + \left(r - s\sqrt{d}\right) + \gamma &= 0 \\ \gamma = -2r \end{align*})
but this makes the third root rational, which is impossible by part (a), and so there can be no root of the form
![](https://latex.codecogs.com/png.latex?\bg_white x = r + s\sqrt{d})
.